Mycoplasma Pneumoniae Consultation System with the Forward Chaining Method at Hams Hospital Kisaran - Nasution, Putri Alfiani; Siddik, Mohd.; Rahayu, Elly (Sistemasi: Jurnal Sistem Informasi, 2024)
Many patients go to Dr. Finera Winda S. Tobing at HAMS Kisaran Hospital for the treatment of Mycoplasma Pneumoniae. Meanwhile, there is only 1 special doctor (specialist) who handles this problem. This makes it difficult for doctors to work optimally because it can cause human error due to fatigue at work, so a system is needed that is able to help doctors carry out initial diagnoses of Mycoplasma Pneumoniae and provide solutions to this problem. Based on the description above, the author implemented an expert system related to Mycoplasma Pneumoniae at HAMS Kisaran Regional Hospital. The author hopes that this system can help the public find out about Mycoplasma Pneumoniae earlier and help doctors diagnose patients. The research method used in this research is qualitative research, which is research that only collects data and explains it descriptively/narratively without having to process it with statistical testing. This research will only utilize data obtained from the research site and input it without changing anything. The results of this research are that the expert system for diagnosing Mycoplasma Pneumoniae is effective and efficient in helping doctors, Dr. Finera Winda S. Tobing and makes it easier for patients to consult because patients can consult with a doctor online and can find out their disease correctly so that this research can truly be achieved to overcome existing problems